Penerapan Good Agriculture Practices (GAP) Terhadap Serapan Hara Fosfor (P) pada Daun Tanaman Kopi Arabika (Coffea arabica L.) di Provinsi Sumatera Utara - Wijoyo, Hadi; Nora, Silvia; Yusuf, Mukhtar (JURNAL AGROPLASMA, 2024)
This research aims to analyze the application of Good Agriculture Practices (GAP) to nutrient absorption in the leaves of Arabica coffee plants (Coffea arabica L.) in North Sumatra Province. Data analysis method is quantitative method. The data analysis technique used in this research is descriptive analysis technique to describe the data that has been collected through field surveys which include field observations, leaf sampling and laboratory analysis results to measure nutrient content. The results showed that the application of GAP, including good soil management, planned fertilization significantly increased nutrient uptake in the leaves. The GAP managed crops showed increased levels of phosphorus compared to those managed conventionally. The application of GAP therefore not only improves soil chemical characteristics, but also increases coffee plant productivity through optimizing nutrient uptake, which can contribute to the sustainability of coffee plantations in North Sumatra. Keywords: GAP, leaf nutrient absorption, arabica coffee, north sumatra